HARNESSING ARTIFICIAL INTELLIGENCE TO STRENGTHEN CUSTOMER TRUST AND ISLAMIC VALUES FOR SUSTAINABLE REPURCHASE BEHAVIOR IN SHARIA BANKING - Istiqomah, Nur Hidayatul; Fu’ad, Moch. Syifaul; Zakiyyah, Wafa Rizquna (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to examine the influence of AI-based service personalization and halal labeling on customers’ purchase intention, with customer trust as a moderating variable, in the context of Islamic banking in Tuban, Indonesia. This research employs a quantitative method. The study population consists of customers of Bank Syariah Indonesia (BSI) and BRI Syariah, with a total of 130 respondents obtained through accidental sampling. Data were collected using questionnaires and analyzed with Structural Equation Modeling (SEM) using the Partial Least Square (PLS) approach. The findings reveal that AI personalization has a positive effect on customer trust, and customer trust positively affects purchase intention. Moreover, customer trust is proven to moderate the relationship between AI personalization and purchase intention. However, halal labeling does not significantly influence purchase intention, as it is perceived as a standard attribute inherently attached to every Islamic banking product. This study concludes that, in the context of Islamic banking, purchase intention is more strongly shaped by customer trust and AI-based personalized services rather than halal labeling.